The Celebration of Cultural Diversity and the Politics of Difference in Safeguarding Intangible Cultural Heritage - Arantes, Antonio (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2014)
The global turn of cultural production gave new significance to objects and ideas that convey senses of localization and/or cultural singularity, raising public interest and institutional concern with inventorying and protecting cultural diversity. The implications of this shift not only concern the so-called creative industries, as this issue was the object of the Convention for the Protection of the Diversity of Cultural Contents and Artistic Expressions approved by UNESCO in its 33rd General Conference (Paris, November 2005). Traditional know-how and forms of expression, as well as exotic landscapes, are used as effective cornerstones for the implementation and promotion of humanitarian as well as social and economic development programs in the poorer regions of the globe. From an intellectual perspective, this renewed awareness of all things local stimulates critical reflection about some epistemological and legal issues related to identification, documentation and promotion of cultural heritage. Among these, intellectual authority associated with the production of inventories, the social consequences of introducing new ingredients in local level politics and cultural production, as well as juridical matters concerning rights of collective intellectual property are some of the concerns of the current debate among scholars and heritage experts on those issues. The present paper aims at contributing to the debate on the questions outlined above, by focusing on the emergent policies of safeguarding intangible cultural heritage. Since cultural heritage is not mechanical and neutral transmission of information from one generation to another, but a social construction, the understanding of its meanings and consequences depends on taking into account its historical context. This being the case, in order to provide concrete background to this discussion, the author refers to the Brazilian case suggesting, however, that it has wider implications.